2013
DOI: 10.3126/jnps.v33i3.9252
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Perinatal Outcome of Neonates with Maternal Hypertensive Disorders in Pregnancy

Abstract: Introduction: Hypertensive disorders of pregnancy seem to be one of the major causes of maternal morbidity and mortality leading to 10-15% of maternal deaths especially in the developing world. This study examines the perinatal outcome of neonates with mothers having hypertensive disorder of pregnancy. Materials and Methods: Seventy three mothers and their newborn babies were selected. Mothers with Gestational hypertension, preeclampsia, eclampsia, chronic hypertension, preeclampsia superimposed on chronic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Many studies reported that hypertension during pregnancy increases the risk of maternal and perinatal, morbidity and mortality. [5][6][7] Comparable findings were observed in a study from Queen Elizabeth Central Hospital (QECH) neonatal ward records where 36.5% of neonates admitted in the ward from April to September 2012 had birth asphyxia.…”
Section: Immediate Parameters and Status Of Neonatesmentioning
confidence: 64%
See 4 more Smart Citations
“…Many studies reported that hypertension during pregnancy increases the risk of maternal and perinatal, morbidity and mortality. [5][6][7] Comparable findings were observed in a study from Queen Elizabeth Central Hospital (QECH) neonatal ward records where 36.5% of neonates admitted in the ward from April to September 2012 had birth asphyxia.…”
Section: Immediate Parameters and Status Of Neonatesmentioning
confidence: 64%
“…[5] Hypertension in pregnancy is defined as either a systolic blood pressure (BP) of ≥140 mm Hg OR a diastolic ≥90 mm Hg. [6] Maternal hypertensive disorders are classified into four types: Chronic hypertension, that is known before pregnancy, or present in the first 20 weeks. New onset of hypertension that develops at or after 20 weeks gestation includes preeclampsia superimposed on chronic hypertension, preeclampsia, and eclampsia and gestational hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations